2023
DOI: 10.1007/s41237-023-00193-3
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian modeling of the Mnemonic Similarity Task using multinomial processing trees

Abstract: The Mnemonic Similarity Task (MST: Stark et al., 2019) is a modified recognition memory task designed to place strong demand on pattern separation. The sensitivity and reliability of the MST make it an extremely valuable tool in clinical settings. We develop new cognitive models, based on the multinomial processing tree framework, for two versions of the MST. The models are implemented as generative probabilistic models and applied to behavioral data using Bayesian graphical modeling methods. We demonstrate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Previously, we demonstrated that the traditional REC correlated with π, while LDI correlated with λ (Lee and Stark, 2023, previously denoted as τ). Our first goal was to assess the relationship among the traditional and modeled metrics in the two datasets (Stark et al, 2013; Trelle et al, 2021).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Previously, we demonstrated that the traditional REC correlated with π, while LDI correlated with λ (Lee and Stark, 2023, previously denoted as τ). Our first goal was to assess the relationship among the traditional and modeled metrics in the two datasets (Stark et al, 2013; Trelle et al, 2021).…”
Section: Resultsmentioning
confidence: 96%
“…Cognitive modeling provides a useful tool for inferring latent psychological variables beyond traditional measurements. Previously, we used cognitive modeling to model subject-level performance on the MST in young adults (Lee and Stark, 2023) using the multinomial processing tree (MPT) framework, a common approach for cognitive modeling of recognition memory tasks. The MPT framework assumes that cognitive processes can be divided into discrete categories or decision points (Fig 1B).…”
Section: Cognitive Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work fits in with other recent process models of performance in this task. One such approach used Multinomial Processing Tress (MPT) to distinguish remembering and discrimination from each other and from guessing [18]. A key advantage of this model is that it leverages previous psychometric calibrations of lure item similarity [9] to support the distinction of discrimination-based processing, as discrimination should get progressively more difficult with higher-similarity items.…”
Section: Discussionmentioning
confidence: 99%
“…The MST LDI is generally quantified as the probability that a lure image is correctly classified as "similar," minus the probability that a foil image is mistakenly classified as "similar". Other analytical methods have been proposed for the MST, but they all require clear distinctions between which images in the test set are lures and foils (21,22). However, in clinically applicable memory tests, the differences between testing images may not be so significant that one group can be classified as "foils" while the others are "lures."…”
Section: Introductionmentioning
confidence: 99%